Facile synthesis of 2, 3-benzodiazepines using one-pot two-step phosphate-assisted acylation–hydrazine cyclization reactions. Issue 21 (16th May 2018) - Sumita, Akinari; Lee, Jinhee; Otani, Yuko; Ohwada, Tomohiko
Abstract : We present a one-pot two-step methodology, in which an unprotected amino is tolerated, for rapidly synthesizing 2, 3-benzodiazepines via phosphate-assisted acylation reaction and hydrazine cyclization reaction. Abstract : Here, we report new methodology for synthesizing 2, 3-benzodiazepines and their analogues by means of phosphate-assisted acylation reaction of 1-arylpropan-2-ones with a carboxylic acid followed by hydrazine cyclization in a one-pot two-step manner. An unprotected amino group is tolerated in this reaction. This method provides a direct access to 2, 3-benzodiazepines containing aromatic 7, 8-dimethoxy and 1- p -aminophenyl groups, which are generally considered important for bioactivity. The presence of 3, 4-dimethoxy or 3-methoxy substitution on the benzene ring of the 1-arylpropan-2-one is important for high regioselectivity in the acylation reaction.